Globalizing IR: Can Regionalism offer a path for other Sub-Disciplines? - (:unkn) unknown (CENTER FOREIGN POLICY & PEACE RESEARCH, 2022)
Global International Relations (IR) research promotes more spaces for a broader spectrum of histories, insights, and theoretical perspectives beyond the conventional dominant Western ones in the IR discipline. The primary goal of this paper is to highlight that the study of Regionalism has a significant role in supporting the initiative of 'globalizing IR' by representing a sub-discipline that is open to new ideas, theories and methods, especially those emanating front non-Western contexts. As such, Regionalism is one of the sub-disciplines of IR and International Political Economy (IPE) with a tremendous potential to showcase global-IR trends. This article utilizes a bibliometric analysis as a proxy for mapping out the diverse and complex intellectual structure of Regionalism as a sub-discipline of IR. Our findings indicate that the remarkable rise in the total number of contributions from non-Western scholars to the Regionalism literature in the last decade suggests that unlike the theory generating mainstream studies Regionalism studies have become dominated by non-European/non-Western contexts.
Keywords: Regionalism; regions; Global-IR and regionalism; bibliometric analysis of regionalism; INTERNATIONAL-RELATIONS IR; RETHINKING; IDEAS